Prevalence and determinants of insufficient vitamin D status in young Canadian Inuit children from Nunavik - Huguette Turgeon O Brien; Doris Gagné
Background: Vitamin D deficiency has reached pandemic levels affecting over one billion people worldwide. However, limited data is available on the prevalence and determinants of vitamin D status of Canadian Indigenous children and no study has been reported in Inuit children from Nunavik. Aim: Therefore, using data collected between 2006 and 2010, we aimed to investigate the prevalence and main determinants of insufficient serum 25-hydroxyvitamin D (s25(OH)D) concentrations in Inuit children attending childcare centres in Nunavik. Methods: This study included 245 Inuit children aged 11 to 54 months. s25(OH)D concentrations were measured by radioimmunoassay. Dietary intakes were assessed using 24-hour recalls. Usual dietary intakes were estimated using the National Cancer Institute method. We used a multiple imputation technique to replace missing values when performing regression analysis. Results: Our findings revealed that 64.5% of children had a s25(OH)D concentration < 75 nmol/L, while 78.1% did not meet the estimated average requirement (EAR) for vitamin D. Vitamin D intake and fluid milk consumption were positively associated with s25(OH)D concentrations, while negative associations were observed with children energy intake, non-alcoholic beverage consumption, body weight, breastfeeding duration and, biological/adoptive/foster parents educational level. Conclusion: Vitamin D inadequacy was highly prevalent and closely aligned with levels observed over the years in non-Indigenous children. Breastfed children who do not receive vitamin D supplementation, overweight and obese children, and children with inadequate milk consumption were at high risk of vitamin D insufficiency. Eating vitamin D rich foods such as fluid milk and seafood along with vitamin D supplementation when needed are recommended.